Detection of β-Globin Gene Polymorphisms Using Real Time PCR-High Resolution Melting Method in Selected Iranian β-Thalassemia Patients - Marashi, Syed Jalal (2011)
β-thalassemia is a common autosomal recessive disorder among the hereditary diseases worldwide. It is caused by the reduced production of functional β-globin which lead to anemia, as a result of point mutations, small deletions or insertions within the β-globin gene which is located as a cluster on the short arm of chromosome 11. More than 200 different mutations of β-globin genes have been identified. β-thalassemia is most prevalent around the Mediterranean. The gene frequency of β-thalassemia in Iran is high and alters significantly from area to area, but around the Caspian Sea and Persian Gulf with more than 10% have the highest rate. Since the Iranian populations are mixture of different ethnic groups and regarding to lack of precise prevalence of common mutations in β-thalassemic patients in Qazvin province of Iran, research project was defined to identify an accurate allele frequency of common mutations in β-thalassemia patients, with Real Time-PCR HRM method.PCR-based strategies and direct sequencing have been carried out to screen β-thalassemia subjects. In this research the Rotor-Gene™ 6000 real time rotary analyzer was applied to amplify a target sequence of DNA to high copy number with incorporation of fluorescent (EvaGreen™) dye prior to performing a High Resolution Melting (HRM) analysis. Samples were then analyzed in the HRM channel according to their dissociation behavior. In this descriptive-analytical study, β-thalassemia chromosomes of l20 affected patients (120 β-thalassemia major) were evaluated. The most common mutation detected among subjects was nucleotide 1 (G to A conversion) of Intervening Sequence (IVS) region 2. Thus, IVS-II-I (G-A) (25.4%), is followed,based on frequency, with IVS-I-110(G-A) (15.4%), IVS-I-5(G-C) (13.3%), FSC-8/9(5.8%), FSC-36/37 (4.6%), Codon 30 ( 2.5%), IVS-I-6(T-C) (2.1%), IVS-I-1(GA) (0.8%). The three mutations IVS-II-1(G-A), IVS-I-110(G-A) and IVS-I-5(G-C) accounted for about 54.2% of all of the mutations. The most common allele being IVSII-I (G-A) with a frequency of 25.4 %. In the rest of samples (29.2%) these 8 mutations were not detected and were remained unknown after analysis with common primer that needs further investigation which is beyond the objectives of the study. A rare Hb Monroe and codon 8 (-AA) mutations from Qazvin province of Iran were also detected.The results derived from HRM analysis were fully in accordance with sequencing. Real time- PCR was produced enough DNA for fluorescent melting analysis, both amplification and analysis could be performed in the same tube, providing a homogeneous, closed-tube system that requires no processing or separation steps without any contamination. Consequently HRM could be a sensitive, simpler and more cost effective way to characterize samples than conventional methods and HRM method could greatly facilitate screening for these 8 β-thalassemia mutations. But the main limitation of HRM is that the precise mutation cannot be readily identified and it thus needs to be coupled with sequencing method.We suggest this rapid and accurate method for molecular screening to detect the common β-thalassemia mutations in the Iranian population as well as in other ethnic groups and nationalities in which β-thalassemia alleles are prevalent.